1994
DOI: 10.1071/ar9940303
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein and trace element metabolism in sheep tissues in response to high and sustained zinc dosages. 1. Characterization and turnover of metallothionein isoforms

Abstract: Romney wether sheep were given ZnO on a regular basis, as required in protocols for the treatment of facial eczema, at either 12 g ZnO fortnight-1 or 12 g ZnO week-1, and the effect of Zn on the synthesis of different metallothionein (MT) isoforms isolated from liver tissue characterized and quantified. Metallothionein isoforms in liver of dosed and non-dosed sheep were quantitatively determined by reverse phase HPLC, with markedly increased concentrations of total MT-Ia protein found in the liver tissue of Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Cd absorption is most commonly affected by the Zn status of animals, and Cd has been demonstrated to increase Zn accumulation in sheep, perhaps by the stimulation of MT production (Doyle & Pfander, 1975;Grace et al 1993;Lee et al 1994). Conversely, Chiy et al (1998) found that a high Zn intake reduces Cd absorption in sheep, suggesting competition between the two elements.…”
Section: Accumulation By the Grazing Animal Of Potentially-toxic Metamentioning
confidence: 99%
See 1 more Smart Citation
“…Cd absorption is most commonly affected by the Zn status of animals, and Cd has been demonstrated to increase Zn accumulation in sheep, perhaps by the stimulation of MT production (Doyle & Pfander, 1975;Grace et al 1993;Lee et al 1994). Conversely, Chiy et al (1998) found that a high Zn intake reduces Cd absorption in sheep, suggesting competition between the two elements.…”
Section: Accumulation By the Grazing Animal Of Potentially-toxic Metamentioning
confidence: 99%
“…The characteristic of Class B elements to form ligands with N and/or S, includes metallothioneins (MT; Cousins, 1985;Lee et al 1994), phytochelatin (Marschner, 1995), complexes with globular proteins (caeruloplasmin; Underwood & Suttle, 1999) and excretion in bile (e.g. Cd; Kiyozumi & Kojima, 1978).…”
mentioning
confidence: 99%